KARAKTERISASI POPULASI DAN POTENSI CACING TANAH UNTUK PAKAN TERNAK DARI TEPI SUNGAI KAHAYAN DAN BARITO - M. A. Firmansyah; Suparman Suparman; Harmini Harmini; I.G.P. Wigena; Subowo Subowo (Research Center for Biology-Indonesian Institute of Sciences, 2014)
The spread of earthworm habitat much larger on the banks of the rivers in Central Kalimantan.The aim of this study was to characterize the habitat of earthworm located on banks of the rivers of Kahayan and Barito. Preparation of soil profile with dimension 1x1 m and a depth of 20 cm was conducted using transect procedure and positioned from dried riverbed up to river embankment. The results showed that earthworms with a larger size identified as Lumbriscus terrestris was mainly found in Kahayan river, while for relatively smaller species, it was found at Barito river identified as Lumbriscus rubellus. The number of L .rubellus populations is more 12 and 522 earthworms per layer than L. terrestris. The shallow of water level for ground water and rough texture was not suitable condition for earthworm habitat at both location. The level of protein and ash content are 30.30 % and 42.78 % respectively and higher compared to L. rubellus i.e 13.28 % and 6.27% respectively.